2019
DOI: 10.1002/slct.201901866
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of 2‐Amino‐6‐(1,2‐dihydro‐4‐hydroxy‐2‐oxoquinolin‐3‐yl)‐4‐arylpyridine‐3‐carbonitriles Catalysed by NbCl5 and Their In Vitro Antimicrobial Studies

Abstract: Synthesis of 2-amino-6-(1, 2-dihydro-4-hydroxy-2-oxoquinolin-3-yl)-4-arylpyridine-3-carbonitrile has been accomplished via NbCl 5 catalysed multicomponent reaction (MCR). The tested compounds showed better potency than Neomycin and a broad spectrum of antibacterial activity against Staphylococcus aureus, Bacillus cereus and Escherichia coli. Similarly some of these have showed good activity against Staphylococcus aureus, Klebsiella planticola and Escherichia coli that were comparable to Ciprofloxacin. Also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For instance, Krishna and colleagues described the synthesis of quinolone–pyridine hybrids 45 in 63–85% yields through a time-efficient four-component reaction of (hetero)aromatic aldehydes 1, malononitrile 2, 3-acetyl-4-hydroxy-2(1 H )-quinolone 44, and an excess of ammonium acetate catalyzed by NbCl 5 (15 mol%) in DMF at 75 °C for 30 min ( Scheme 11 ). 62 The compounds 45a–p were screened for their antibacterial activity against two Gram-positive ( Staphylococcus aureus and Bacillus cereus ) and three Gram-negative ( Klebsiella planticola , Escherichia coli , and Pseudomonas aeruginosa ) bacterial strains using Ciprofloxacin hydrochloride as a standard drug. It was found that compound 45e (R = 4-MeOC 6 H 4 ) exhibited an excellent activity against Staphylococcus aureus and Bacillus cereus with a MIC value of 2.34 μg mL −1 , in comparison to Ciprofloxacin hydrochloride (MIC = 4.68 and 2.34 μg mL −1 , respectively).…”
Section: Multicomponent Synthesis Of Bioactive 2-pyridone Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Krishna and colleagues described the synthesis of quinolone–pyridine hybrids 45 in 63–85% yields through a time-efficient four-component reaction of (hetero)aromatic aldehydes 1, malononitrile 2, 3-acetyl-4-hydroxy-2(1 H )-quinolone 44, and an excess of ammonium acetate catalyzed by NbCl 5 (15 mol%) in DMF at 75 °C for 30 min ( Scheme 11 ). 62 The compounds 45a–p were screened for their antibacterial activity against two Gram-positive ( Staphylococcus aureus and Bacillus cereus ) and three Gram-negative ( Klebsiella planticola , Escherichia coli , and Pseudomonas aeruginosa ) bacterial strains using Ciprofloxacin hydrochloride as a standard drug. It was found that compound 45e (R = 4-MeOC 6 H 4 ) exhibited an excellent activity against Staphylococcus aureus and Bacillus cereus with a MIC value of 2.34 μg mL −1 , in comparison to Ciprofloxacin hydrochloride (MIC = 4.68 and 2.34 μg mL −1 , respectively).…”
Section: Multicomponent Synthesis Of Bioactive 2-pyridone Derivativesmentioning
confidence: 99%
“…Alternatively, Krishna and colleagues described the synthesis of quinolone–pyridine hybrids 45 via an NbCl 5 -catalyzed four-component reaction and discussed in Section 2.2. Antibacterial activity ( Scheme 11 ), 62 were also screened for their antifungal activity against Candida albicans , Candida parapsilosis , Candida glabrata , Candida aaseri , Aspergillus niger , and Issatchenkia hanoiensis using Miconazole as a standard drug. Particularly, the compound 45n (R = naphthalene-2-yl) showed the highest activity against tested Candida and fungal pathogens with MIC values ranging from 1.67 to 9.37 μg mL −1 , in comparison to Miconazole (MIC = 4.68–9.37 μg mL −1 ).…”
Section: Multicomponent Synthesis Of Bioactive 2-pyridone Derivativesmentioning
confidence: 99%
“…The quinolonic moiety is a pharmacophoric group and it is used for the development of new substances. It is possible find on the literature a wide variety of biological activities (DHIMAN et al, 2019), such as: anticancer (RELITTI et al, 2020;GAO et al, 2019;ZHAO & YU 2018;CHEN et al, 2004), antifungal (KHAMKHENSHORNGPHANUCH et al, 2020ZANG, 2019;EL-DESOKY et al, 2018), antioxidant JAYASHREE et al, 2010;CHUNG & WOO, 2001), antimalarial (BETECK et al, 2019;FAN et al, 2018;WUBE et al, 2014), antibacterial (LI & CLARK, 2020;KOIDE et al, 2019;KRISHNA & SARVESWARI, 2019;VALADBEIGI & GHODSI, 2017;PANDA et al, 2015;KERNS et al, 2003) and antimycobacterial (BETECK et al, 2020;BETECK et al, 2019;HONG et al, 2017;PUCCI et al, 2010) (Figure 2). Source: Adapted from antifungal: ZANG, 2019;antibacterial: PANDA et al, 2015;antioxidant: JAYASHREE et al, 2010.;antimycobacterial:PUCCI et al, 2010;antineoplasic: GAO et al, 2019 antimalarial: WUBE et al, 2014.…”
Section: Introductionmentioning
confidence: 99%